Volumetric MRI assessment of brain regions in patients with refractory obsessive-compulsive disorder - Atmaca, Murad; Yildirim, Hanefi; Ozdemir, Huseyin; Aydin, Ayse; Tezcan, Ertan; Ozler, Sinan (Pergamon-Elsevier Science Ltd, 2006)
No prior study to date has examined the comparisons of the structures that have been implicated in obsessive-compulsive disorder (OCD) in patients with refractory OCD, those who are treatment-responded and healthy controls concurrently. Therefore, we performed a volumetric MRI study in patients with refractory OCD, those with treatment responding OCD and healthy controls. Morphometric MRI was used to compare in thirty patients with OCD and ten healthy controls. Of the patient group, ten were first applying patients, ten were treatment-responded and the rest were refractory OCD patients. As a whole group, OCD patients had increased white matter volume than healthy controls. First applying patients had significantly smaller left and right orbito-frontal cortex (OFC) volumes compared with treatment-responded patients and healthy controls, with a significant difference between refractory patients and treatment-responded patients and with no significant difference was found between the volume of first applying patients compared to that of refractory patients. Anterior cingulate exhibited a near-significant difference only between first applying patients and healthy controls on left side. First applying patients had significantly greater left and right thalamus volumes compared with treatment-responded patients and healthy controls and there was a considerable difference in regard to thalamic volumes between refractory patients and treatment-responded patients. Taken together, our findings suggest that reductions in OFC and increase in thalamic volumes may be associated with refractoriness of OCD and may not be due to changes in cingulate and caudate regions. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: anterior cingulated; brain regions; MRI; orbito-frontal cortex (OFC); refractory; volume